IMPLEMENTATION OF PRODUCTION COST CALCULATIONS USING THE PROCESS COSTING METHOD IN THE FACTORY - Eka Rumanintya; Liana Putri (Jurnal Pelayanan Hubungan Masyarakat, 2023)
One of the factors that will affect the company's survival is pricing. Price is a measure to be able to know how much the value of a good and service. The price also determines the success or failure of goods or services will be sold in the market, because the price is the value of an item expressed in units of money. In addition, the price is used as a benchmark or starting point for other pricing or price is a suggestion liaison between buyers and sellers. This means that prices are determined by demand and supply will be a product or service that has been customized.